Problems of Criminal and Legal Qualification of Domestic Violence - Yu. V. Orlov (Law and Safety)
The subject matter of the research is theoretical and applied problems of criminal and legal qualification of domestic violence. Its purpose is to form propositions for solving these problems. The latter include the difficulties of unambiguous interpretation and legal assessment of the features of a socially dangerous act provided by the Art. 126-1 of the Criminal Code of Ukraine, and the features of “systematic”, establishing socially dangerous consequences and causal relation and distinguishing domestic violence from related corpus delicti of criminal offenses.